Chrysomya bezziana as a Causative Agent of Human Myiasis in Fars Province, Southern Iran - A Faramarzi; AR Rasekhi; M Kalantari; GR Hatam (Journal of Arthropod-Borne Diseases, 2009)
Myiasis is the invasion of body tissues of humans or animals by the larvae of the Diptera or two-winged flies. The various forms of myiasis may be classified from clinical or entomological point. This study describes the existence of Chrysomya bezziana (Diptera: Calliphoridae) cases as a causative agent of myiasis in 18 and 87 year-old men in two different regions in Fars Province. To our knowledge, this is the first observation of mentioned species in this province.